Conservation easements in context: a quantitative analysis of their use by The Nature Conservancy. Issue 9 (1st April 2007) - Kiesecker, Joseph M.; Comendant, Tosha; Grandmason, Terra; Gray, Elizabeth; Hall, Christine; Hilsenbeck, Richard; Kareiva, Peter; Lozier, Lynn; Naehu, Patrick; Rissman, Adena; Shaw, M Rebecca; Zankel, Mark
Abstract : Conservation easements have become the principal tool used by land trusts to preserve habitat and open space. However, anecdotal evidence has led some to question whether easements actually deliver conservation value. Our analysis of data from 119 easements held by The Nature Conservancy (TNC), spanning eight states and 20 years (1984–2004), is the first study to examine temporal patterns in the stated goals of, and activities allowed under, conservation easements. We found that these easements operate in accordance with conservation principles: 96% of sampled easements have identified biological targets, 84% are within TNC priority sites, and 79% are adjacent to protected areas. Easement usage has also become more strategic; recently established easements are more likely than older easements to be large and to include a management plan that focuses on biological targets. The one shortcoming we uncovered is a lack of biological monitoring. Although 92% of sampled easements have been monitored for legal compliance in the past 3 years, only 19.8% of biological targets have been monitored quantitatively. It is clear that we cannot draw conclusions regarding easement effectiveness unless we implement more systematic monitoring.